Stable isotope potential of Northern Vietnam stalagmites: A 51-cave survey with the Hendy test and U/Th analysis - Thuy Nguyen, Duong; Chi Nguyen, Dung; Thi An, Thuy; Yuan Huang, Chun-; Chou Shen, Chuan-; György, Czuppon; Van Bui, Dong; Ngoc Nguyen, Linh; Wei Chiang, Hong-; Gau Chen, Yue-; Vu Van, Ha; Minh Nguyen, Quang; et al. (Vietnam Journal of Earth Sciences, 2025)
Northern Vietnam’s karst landscapes offer an untapped potential for paleo-monsoon research, complementing the extensive speleothem records of Southwest China. Here, we surveyed 51 caves across seven provinces, targeting those with humidity exceeding 95% from 2017 to 2024, and collected 127 broken stalagmites to evaluate their stable-isotope potential (δ18O, δ13C) as paleoclimate proxies. Focusing on caves in Hoa Binh and nearby karst-rich regions, we applied Hendy tests to 56 subsamples of eight layers on four stalagmites, NS3, HS3, HS7, and HS16, to assess the isotopic equilibrium conditions. The deposition intervals of the four stalagmites, determined using U/Th dating, range from 36 to 60 thousand years ago (ka). Small 1-sigma variations of ±0.04−0.20‰ in coeval δ18O values across all eight layers suggest deposition under near oxygen isotope equilibrium. Combined with fast growth rates exceeding 0.09 mm/year, this evidence suggests high-resolution potential for paleohydroclimate reconstruction using stalagmite δ18O data. However, one-sigma variations of ±0.04−0.71‰ of coeval δ13C data reflect relatively large carbon isotopic fractionation during the degassing process. It suggests that stalagmite δ13C records from these caves should be carefully evaluated before use in paleoclimate reconstructions.